Influence of cultural heritage on hotel prices, occupancy and profit: Theory and evidence. (October 2016) - Mathur, Sameer; Dewani, Prem Prakash
This article presents a theoretical model of a heritage hotel setting prices for two types of hotel rooms distinguished by their level of heritage. The authors analyse the model using game theory. They derive the profit-maximizing prices as a function of the differentiation between the hotel rooms and the relative proportion of each type of hotel room. They also measure the occupancy rate of each type of room and the total profit made by the hotel in response to the optimal prices. The article also presents an empirical study of hotel rooms located near the Eiffel Tower in Paris to complement the theoretical analysis. The study finds that rooms offering a view of the Eiffel Tower are priced significantly higher than rooms not offering this view. Moreover, the price premium imposed for the heritage view is relatively higher at more expensive hotels.